2014
DOI: 10.1089/jir.2013.0077
|View full text |Cite
|
Sign up to set email alerts
|

OM85-BV Induced the Productions of IL-1β, IL-6, and TNF-α via TLR4- and TLR2-Mediated ERK1/2/NF-κB Pathway in RAW264.7 Cells

Abstract: 1Broncho-Vaxom (OM85-BV) is an extract mixture from 8 strains of Gram + and Gram -bacteria and plays an important role in anti-infection immune response by regulating macrophage activity and cytokine productions. However, the mechanism by which OM85-BV enhances the cytokine expression is still obscure. In this study, we evaluated the effects of OM85-BV on the productions of interleukin (IL)-1b, IL-6, and tumor necrosis factor-a (TNF-a) in RAW264.7 murine macrophages. Exposure of RAW264.7 cells to 100 mg/mL OM8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 34 publications
7
56
0
4
Order By: Relevance
“…Furthermore, our results showed that MyD88 was necessary to augment the levels of proIL-1α and proIL-1β, which are canonical NF-κB targets, downstream of OM-85. Along these lines, previous findings showed a central role for TLRs, MyD88, and activation of downstream NF-κB signaling by OM-85485161. In addition, we show here the involvement of the adaptors MyD88 and Trif in the induction of type I IFN, inferring the implication of TLR3 or TLR4 upon OM-85 treatment51.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, our results showed that MyD88 was necessary to augment the levels of proIL-1α and proIL-1β, which are canonical NF-κB targets, downstream of OM-85. Along these lines, previous findings showed a central role for TLRs, MyD88, and activation of downstream NF-κB signaling by OM-85485161. In addition, we show here the involvement of the adaptors MyD88 and Trif in the induction of type I IFN, inferring the implication of TLR3 or TLR4 upon OM-85 treatment51.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study demonstrated that TLR-4 and TLR-2 interact with components of bacterial lysates through extracellular signal-regulated kinase-1/2 and nuclear factor-kB pathways, resulting in increased secretion of IL-1b and IL-6 and tumor necrosis factor-a. 34 Bacterial ribosomal extracts also acted as TLR-7/8 agonists and induced antiviral cytokines in mononuclear cells. 35 However, TLR-4, endosomal TLRs, and RIG-1elike receptor were not involved in bacterial lysate activity and signaling, whereas bacterial lysate OM-85 induced cytokine secretion through the nuclear factorkB and mitogen-associated protein kinase pathways, which are activated downstream of most pattern recognition receptors.…”
Section: Interaction Of Bacterial Lysates With Pattern Recognition Rementioning
confidence: 99%
“…TLR4-mediated activation of ERK1/2 is known to induce expression of proinflammatory cytokines, including TNF-a and IL-1b (DeFranco et al, 1998;Schaefer et al, 2005;Luan et al, 2014). Recent reports also indicate that these cytokines may negatively regulate PGC-1a expression and MB in a variety of cell types, including renal proximal tubule cells and skeletal muscle cells (Tran et al, 2011;Remels et al, 2013).…”
Section: Downloaded Frommentioning
confidence: 99%